c.1 - Jha, L. K. (New Delhi, 1985)
This book covers following topics: To operate controls without aggrandisement of the bureaucracy; to fight inflation without curbing investment; to generate employment without making two men to do the work of one; to develop indigenous technology without denying ourselves access to external technology.
Keywords: Economic development-India